A review of the genus Maimuna Lehtinen, 1967 (Araneae, Agelenidae) in Turkey, with a description of a new species - Dimitrov, Dragomir (Zootaxa, 2022)
The records of the agelenid spider genus Maimuna Lehtinen, 1967 from Turkey are reviewed. A new species, Maimuna anatolica sp. n. is described from Muğla Province, Anatolia. The other two Turkish species of the genus are illustrated and re-diagnosed. Some discrepancies in the different diagnoses of the genus Maimuna are pointed out and discussed.